MicroRNA-650 expression is influenced by immunoglobulin gene rearrangement and affects the biology of chronic lymphocytic leukemia - Mraz, Marek; Dolezalova, Dasa; Plevova, Karla; Stano Kozubik, Katerina; Mayerova, Veronika; Cerna, Katerina; Musilova, Katerina; Tichy, Boris; Pavlova, Sarka; Borsky, Marek; Verner, Jan; Doubek, Michael; et al. (Blood, 2012)
MicroRNAs (miRNAs) play a key role in chronic lymphocytic leukemia as well as in normal B cells. Notably, miRNA gene encoding miR-650 and its homologs overlap with several variable (V) subgenes coding for lambda immunoglobulin (IgLλ). Recent studies describe the role of miR-650 in solid tumors, but its role in chronic lymphocytic leukemia (CLL) has not yet been studied. Our experiments demonstrate that miR-650 expression is regulated by coupled expression with its host gene for IgLλ. This coupling provides a unique yet unobserved mechanism for microRNA gene regulation. We determine that higher expression of miR-650 is associated with a favorable CLL prognosis and influences the proliferation capacity of B cells. We also establish that in B cells, miR-650 targets proteins important in cell proliferation and survival: cyclin dependent kinase 1 (CDK1), inhibitor of growth 4 (ING4), and early B-cell factor 3 (EBF3). This study underscores the importance of miR-650 in CLL biology and normal B-cell physiology.
Keywords: dospělí; Female; Cell Line, Tumor; Adult; genová přestavba; ženské pohlaví; Cell Cycle; Leukemia, Lymphocytic, Chronic, B-Cell; Genes, Immunoglobulin Light Chain; lidé; staging nádorů; Aged, 80 and over; geny pro imunoglobuliny; prognóza; buněčný cyklus; Middle Aged; regulace genové exprese; Male; Aged; chronická lymfatická leukemie; mikro RNA; Prognosis; Gene Rearrangement; MicroRNAs; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Gene Expression Regulation; Genes, Immunoglobulin; Neoplasm Staging; geny pro lehké řetězce imunoglobulinů; nádorové buněčné linie; Humans